Uprawnienia do reprezentowania małżonki w koncepcjach glosatorów i komentatorów - Szymańska, Aleksandra (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
The subject of this article is an analysis of the opinions of glossators and commentators on a husband's rights to represent his wife. The opinions of such jurists as Accursius, Odofredus, Cynus de Pistoia, Bartolus de Saxoferrato, Baldus de Ubaldis and Paulus de Castro were analyzed. The glossators and commentators recognized that a woman could act in her own affairs and could also give a mandatum. The spouse seemed to be the natural mandatary. Sometimes, however, the wife made no orders regarding her affairs. Although the husband should respect the boundaries of the mandate, just like any other mandatary, he could represent his wife by law in other matters independent of the mandatum. This was accompanied by the general conviction that the husband is the wife's legal administrator, either as her procurator or as persona coniuncta.
Keywords: marriage; mandatum; glossators; commentators